2015
DOI: 10.1016/j.conbuildmat.2015.02.094
|View full text |Cite
|
Sign up to set email alerts
|

Gypsum efflorescence on clay brick masonry: Field survey and literature study

Abstract: h i g h l i g h t s 28 Belgian cases of persistent masonry efflorescence were investigated. Gypsum is the major persistent efflorescence component. The formation mechanism is related to moisture transport and not to air pollution. Both brick and mortar can be the source of gypsum efflorescence. Many aspects remain hypothetical, rising important research questions. a b s t r a c tBelgian masonry facades are being increasingly affected by unsightly persistent efflorescence. This results in disappointed customers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Efflorescence refers to the phenomenon which cement hydration product Ca(OH) 2 in the pore solution and the external environment of the molar concentration gradient driven continues to lose and cause of C─S─H gel and ettringite continuous decalcified dissolution, resulting in calcium ion concentration in the pore solution declining, pH continued to decrease, and the hydration products gradually lose gelation when cement‐based materials in soft water or other media environment. For buildings, it is not conducive to the sound insulation performance, fire performance and decoration engineering quality control . The results showed that the Ca(OH) 2 of hydration product had the following relationship with C─S─H. Ca(OH) 2 and C─S─H remained relatively stable when the concentration of calcium ion in the pore solution is high; when the pore solution c (Ca 2+ ) < 20 mmol/L, Ca(OH) 2 begins to dissolve; when the pore solution c (Ca 2+ ) < 4 mmol/L, C‐S‐H begins to decalcification dissolve; when the pore solution c (Ca 2+ ) < 2 mmol/L, the chemical loss of concrete reaches the maximum, and the residue of this stage is the silica gel with no binding properties. …”
Section: The Mathematical Model Of Efflorescence Of Cement‐based Matementioning
confidence: 99%
See 1 more Smart Citation
“…Efflorescence refers to the phenomenon which cement hydration product Ca(OH) 2 in the pore solution and the external environment of the molar concentration gradient driven continues to lose and cause of C─S─H gel and ettringite continuous decalcified dissolution, resulting in calcium ion concentration in the pore solution declining, pH continued to decrease, and the hydration products gradually lose gelation when cement‐based materials in soft water or other media environment. For buildings, it is not conducive to the sound insulation performance, fire performance and decoration engineering quality control . The results showed that the Ca(OH) 2 of hydration product had the following relationship with C─S─H. Ca(OH) 2 and C─S─H remained relatively stable when the concentration of calcium ion in the pore solution is high; when the pore solution c (Ca 2+ ) < 20 mmol/L, Ca(OH) 2 begins to dissolve; when the pore solution c (Ca 2+ ) < 4 mmol/L, C‐S‐H begins to decalcification dissolve; when the pore solution c (Ca 2+ ) < 2 mmol/L, the chemical loss of concrete reaches the maximum, and the residue of this stage is the silica gel with no binding properties. …”
Section: The Mathematical Model Of Efflorescence Of Cement‐based Matementioning
confidence: 99%
“…For buildings, it is not conducive to the sound insulation performance, fire performance and decoration engineering quality control. 8,9 The results showed that the Ca(OH) 2 of hydration product had the following relationship with C─S─H.…”
mentioning
confidence: 99%
“…Moreover, salt solubility is not a measure of aggressiveness of a given solution although it is true that salts with the highest solubility are more dangerous [10]. The main and direct cause of salt aggressiveness towards the mineral material is not the salt solution itself but first of all crystallisation of salt from this solution [8,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A wider approach to the assessment of salinity of mineral materials is proposed in "A guide to salt damp in historic and older buildings" [2], according to which the determination of salt content in materials should be based on a full chemical analysis of cations and anions using, e.g., ion chromatography for the cations and coupled plasma atomic emission spectrometry for the anions. Additionally, full identification of the type and amount of salt facilitates the selection of methods for desalination of walls, which in consequence allows for an effective process of their drying and carrying out conservation work [9,11,[16][17][18][19]. Depending on the type and content of salt, the process of degradation of functional properties takes place with different intensity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, whitish deposits of water soluble salts are alkali sulfate or sodium chloride, which generally appear soon after erection of the facade. In addition, the appearance of white efflorescence depends on environmental circumstances, material parameters of bricks, mortar and concrete blocks, and may additionally be influenced by treatments of the façade (Brocken and Nijland, 2004; Chwast et al, 2015). According to the existing researches, a physicochemical model was developed to explain the key features and the formation of efflorescence (Kresse, 1982, 1987; Vickers and Moukwa, 1996; Dow and Glasser, 2003).…”
Section: Introductionmentioning
confidence: 99%